The surface cell cooling coefficient: a standard to define heat rejection from lithium ion battery pouch cells - Hales,A; Marzook,MW; Bravo,Diaz L; Patel,Y; Offer,G (Journal of The Electrochemical Society, 2020)
There is no universal and quantifiable standard to compare a given cell model's capability to reject heat. The consequence of this is suboptimal cell designs because cell manufacturers do not have a metric to optimise. The Cell Cooling Coefficient for pouch cell tab cooling (CCC tabs ) defines a cell's capability to reject heat from its tabs. However, surface cooling remains the thermal management approach of choice for automotive and other high-power applications. This study introduces a surface Cell Cooling Coefficient, CCC surf which is shown to be a fundamental property of a lithium-ion cell. CCC surf is found to be considerably larger than CCC tabs , and this is a trend anticipated for every pouch cell currently commercially available. However, surface cooling induces layer-to-layer nonuniformity which is strongly linked to reduced cell performance and reduced cell lifetime. Thus, the Cell Cooling Coefficient enables quantitative comparison of each cooling method. Further, a method is presented for using the Cell Cooling Coefficients to inform the optimal design of a battery pack thermal management system. In this manner, implementation of the Cell Cooling Coefficient can transform the industry, by minimising the requirement for computationally expensive modelling or time consuming experiments in the early stages of battery-pack design.